Nanotechnology-Based Approaches for the Detection of SARS-CoV-2 - Gupta, Ritika; Sagar, Poonam; Priyadarshi, Nitesh; Kaul, Sunaina; Sandhir, Rajat; Rishi, Vikas; Singhal, Nitin Kumar (Frontiers in Nanotechnology, 2020)
The recent emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as pandemic is proven to be a severe medical burden and affected - socio-economic activities globally. Proven transmission of this virus occurs through airborne droplets from infected person. Recent upsurge in the number of infected individuals has already crossed the number of intensive care units available to the patients. These extraordinary circumstances has elicited the need of development of diagnostic tools for the detection and henceforth, containment of the disease. Conventional techniques such as quantitative real time polymerase chain reaction (qRT-PCR) and chest computed tomography (CT)-scans have been used extensively for the diagnostic purposes. However, several challenges are confronted including prolonged assay requirements, labour-intensive, low sensitivity and unavailability of these resources in remote locations. Such challenges pose an urgent need of fast, sensitive and accurate diagnosis techniques for timely detection and treatment of the COVID-19 infections. Point of care (PoC) biosensors which includes paper and chip-based diagnostic systems are rapid, cost effective, and are user friendly. In this article nanotechnology-based potential biosensor for the detection of SARS-CoV-2 are discussed with particular emphasis on lateral flow assay (LFA), surface enhanced Raman scattering (SERS)-based biosensor, localized surface plasmon resonance (LSPR)-based biosensor, Förster resonance energy transfer (FRET), electrochemical biosensor and artificial intelligence-based biosensors. Several biomolecules such as nucleic acid, antibody/enzyme or aptamer can serve as potential detection molecule on an appropriate platform such as graphene oxide, nanoparticles or quantum dots. An effective biosensor can be developed by using appropriate combinations of nanomaterials and technologies.